2011
DOI: 10.1271/bbb.110407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Conditions on the α-Glucosidase Inhibitory Activity of Mulberry Leaves

Abstract: Mulberry leaves have been used as the sole food for silkworms in sericulture, and also as a traditional medicine for diabetes prevention. Mulberry leaf components, for example 1-deoxynojirimycin (1-DNJ), inhibit the activity of -glucosidase and prevent increased blood glucose levels, and they are highly toxic to caterpillars other than silkworms. The -glucosidase inhibitory activity of mulberry leaves changes with the season, but it is unknown which environmental conditions influence the -glucosidase inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…However, the correlation coefficients with total temperature in their study were high at r = 0.92 (P = 0.02) in 2009 and r = 0.80 (P = 0.04) in 2010, suggesting a similar trend to the present study (data not shown). Kimura et al (2007) and Nakanishi et al (2011) reported that the DNJ contents in leaves peaked in August, and were affected by temperature. In our study, the DNJ contents in mulberry leaves increased slightly from late May to mid-July, peaked in August, and then decreased sharply after late August.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the correlation coefficients with total temperature in their study were high at r = 0.92 (P = 0.02) in 2009 and r = 0.80 (P = 0.04) in 2010, suggesting a similar trend to the present study (data not shown). Kimura et al (2007) and Nakanishi et al (2011) reported that the DNJ contents in leaves peaked in August, and were affected by temperature. In our study, the DNJ contents in mulberry leaves increased slightly from late May to mid-July, peaked in August, and then decreased sharply after late August.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we hypothesized that the harvest time may also affect the functional component concentrations in mulberry leaves. Kimura et al (2007) and Nakanishi et al (2011) reported that the contents of DNJ and α-glucosidase inhibitors increased in August, the hottest month of the year. In terms of polyphenol contents in mulberry leaves, Lee and Choi (2012) reported that the chlorogenic acid and flavonols contents were highest in May when leaves were harvested three times per year (in May, July, and September), although their results did not document seasonal changes in chlorogenic acid and flavonols contents.…”
Section: Introductionmentioning
confidence: 99%
“…[2324] Among the proposed hypoglycemic FM components, 1-DNJ is one of the mostly studied compounds due to its α-glucosidase inhibitory role which is well established. [1625] Subsequently, a great effort has been made to improve the yield of 1-DNJ from natural resources such as the mulberry leaf and other microorganisms. [17] The present study reported the anti-diabetic activity of a commercial FM product to be effective at a dose as low as 1 mg/kg, which is equivalent to 10 mg/kg dried white mulberry (桑白皮 Sāng Bái Pí) leaf and is a much lower dose than what has been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…[151617] Studies on human beings have revealed that a 1-DNJ–enriched FM preparation is an effective hypoglycemic agent in control and type 2 DM patients. [918] However, a limited number of studies have been conducted on the hypoglycemic activity of purified 1-DNJ in diabetic animals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the anti-obesity effects, some critical adverse effects of these medications such as gastro-intestinal effects [14], increases in blood pressure and pulse rate [15], and increased incidence of mood-related disorder are reported [16]. …”
mentioning
confidence: 99%